Ageing Together: Interdependence in the Memory Compensation Strategies of Long-Married Older Couples - Harris, Celia B.; Sutton, John; Keil, Paul G.; McIlwain, Nina; Harris, Sophia A.; Barnier, Amanda J.; Savage, Greg; Dixon, Roger A. (Frontiers in Psychology, 2022)
People live and age together in social groups. Across a range of outcomes, research has identified interdependence in the cognitive and health trajectories of ageing couples. Various types of memory decline with age and people report using a range of internal and external, social and material strategies to compensate for these declines. While memory compensation strategies have been widely studied, research so far has focused only on single individuals. We examined interdependence in the memory compensation strategies reported by spouses within 58 older couples. Couples completed the Memory Compensation Questionnaire, as well as an open-ended interview about their memory compensation practices. We found that internal, intra-individual memory compensation strategies were not associated within couples, but external, extra-individual strategies showed interdependence. Individuals’ scores on material/technological compensation strategies were positively correlated with their partners’. Reported reliance on a spouse was higher for men and increased with age. Our open-ended interviews yielded rich insights into the complex and diverse resources that couples use to support memory in day-to-day life. Particularly evident was the extent of interaction and coordination between social and material compensation, such that couples jointly used external compensation resources. Our results suggest that individuals’ reports of their compensation strategies do not tell the whole story. Rather, we propose that older couples show interdependence in their memory compensation strategies, and adopt complex systems of integrated material and social memory compensation in their day-to-day lives.